1988
DOI: 10.1051/parasite/1988636448
|View full text |Cite
|
Sign up to set email alerts
|

Zoonotic parasite infections of the Arabian sacred baboonPapio hamadryas arabicusThomas in Asir Province, Saudi Arabia

Abstract: SUMMARY. Evidence of zoonotic parasite infection was recorded in the faeces of the Arabian Sacred Baboon in human populated residential and non-residential areas in Asir, Southwestern Saudi Arabia. Cysts of Giardia intestinalis and Entamoeba histolytica, and ova of Hymenolepis nana, Enterobius vermicularis, Ascaris sp., Trichuris sp., and a hookworm were encountered in 45 (about 39 %) of 115 faecal samples examined. A higher rate of infection was observed in the residential areas. Most of the parasites recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 5 publications
0
12
1
Order By: Relevance
“…Other studies however found baboons usually infected with various helminths (Nasher 1988;Murray et al 2000;Mutani et al 2003). The fact that we did not find any parasites might be the result of the number of samples, the animals' immune status and health condition, the deworming regime, hygienic management and low density of the animals in the enclosure.…”
Section: (48%)contrasting
confidence: 48%
“…Other studies however found baboons usually infected with various helminths (Nasher 1988;Murray et al 2000;Mutani et al 2003). The fact that we did not find any parasites might be the result of the number of samples, the animals' immune status and health condition, the deworming regime, hygienic management and low density of the animals in the enclosure.…”
Section: (48%)contrasting
confidence: 48%
“…It has been estimated that 50 million people develop hemorrhagic amebic colitis and extraintestinal abscesses, resulting in 100,000 deaths annually (Walsh 1988). In addition to its occurrence in humans, E. histolytica is known to be found in captive and wild-trapped nonhuman primates such as macaque monkeys, orangutans, and baboons (Myers and Kuntz 1968;Reardon and Rininger 1968;Sano et al 1980;Eberhard 1981;Collet et al 1986;Beaver et al 1988;Nasher 1988;Ghandour et al 1995;Muriuki et al 1998). Therefore, E. histolytica infections in nonhuman primates may have zoonotic importance (Smith and Meerovitch 1985).…”
Section: Introductionmentioning
confidence: 88%
“…It has been reported that E. histolytica is commonly found in the feces of nonhuman primates such as macaques and baboons (Myers and Kuntz 1968;Reardon and Rininger 1968;Sano et al 1980;Eberhard 1981;Collet et al 1986;Nasher 1988;Ghandour et al 1995). Indeed, invasive amebiasis in nonhuman primates has also been demonstrated (Amyx et al 1978;Loomis et al 1983;Palmieri et al 1984;Beaver et al 1988), suggesting that E. histolytica infection in nonhuman primates may be an important zoonosis (Smith and Meerovitch 1985;Muriuki et al 1998).…”
Section: Introductionmentioning
confidence: 99%